High-throughput underwater elemental analysis by μJ-laser-induced breakdown spectroscopy at kHz repetition rates: part I, ultrasound-enhanced optical emission spectroscopy towards application perspectives. Issue 12 (16th October 2020) - Xue, Boyang; You, Yi; Gornushkin, Igor; Zheng, Ronger; Riedel, Jens
Abstract : Ultrasound-assisted uJ-laser-indcued underwater plasma at kHz repetition rates. Abstract : In recent years, laser-induced breakdown spectroscopy (LIBS) has gained significant attention as a means for simple elemental analyses. The suitability of LIBS for contactless analysis allows it to be a perfect candidate for underwater applications. While the majority of LIBS systems still rely upon sub-kHz pulsed lasers, this contribution introduces 10s-kHz low pulse-energy lasers into underwater LIBS to improve the throughput and statistical validity. Interestingly, the spectral component significantly changed above a critical laser repetition-rate threshold. Spectral lines of atomic hydrogen and oxygen stemming from water become visible beyond a ∼10 kHz repetition rate. This observation suggests a different plasma dynamic compared to low repetition rates. When the pulse-to-pulse interval becomes sufficiently short, a cumulative effect begins to be significant. Apparently, the new phenomena occur on a timescale corresponding to a threshold rate of ∼10 kHz, i.e. ∼100 μs. Analytically, the high repetition rates result in improved statistical validity and throughput. More plasma events per unit time allowed the use of low efficiency Echelle spectrometers without compromising on the analytical performance. Meanwhile, the presence of H I and O I out of the water (as the matrix) also offers internal standardization in underwater elemental analysis. Since the laser fluence was on the lower edge of the plasma threshold, an additional ultrasound source was introduced to induce external perturbation, which significantly improved the plasma formation stability. A huge advantage of LIBS is the possibility of detecting almost all elements within a sample simultaneously. Throughout the periodic table, chlorine is one of the most challenging elements. Consequently, Ca 2+ and Na + were used as samples to demonstrate the capability of this high repetition-rate LIBS platform. As an ambitious benchmark for our system, chlorine detection in water was also discussed.